Clinical and hemodynamic insights into the use of internal iliac artery balloon occlusion as a prophylactic technique for treating postpartum hemorrhage. (2nd December 2021) - Li, Zhongyou; Chen, Yu; Zeng, Xiaoxi; Stephen, Salerno; Li, Yi; Li, Huafeng; Dong, Lihua; He, Teng; Zhang, Shihong; Yang, Pei; Jiang, Wentao; Fan, Haidong
Abstract: Recently, the effectiveness of internal iliac artery balloon occlusion (IIABO) for treating postpartum hemorrhage caused by pernicious placenta previa (PPP) has been questioned. We conducted a retrospective analysis and hemodynamic simulation to assess the IIABO's effectiveness. The retrospective analysis involved 480 patients with PPP, among which 288 underwent IIABO treatment and the remaining 192 were used as controls. Blood loss and preoperative indicators were recorded, and multiple regression analysis was applied to test the effect of preoperative indicators on blood loss. Hemorrhage mechanisms were simulated using a numerical model. Results suggested that no significant difference in blood loss (1836 ± 1440 ml vs. 1784 ± 1647 ml, p  = 0.22) was observed between the two groups. In addition, preoperative indicators, including age, weight, gestational age, gravidity, parity, blood type, anemia, or diabetes, were not associated with blood loss. In the simulation, after the intra-iliac artery was blocked, blood loss was caused by a reversed flow in the intrapelvic arteries, uterine veins, and uterine venules. The ratio of the time-averaged hemorrhage velocity (TAHV) in the balloon group to that in the control group was lower than that obtained in a clinical study (13.0% vs. 88.9%); in the presence of collateral circulation, blood loss occurred from collateral circulation and uterine venules after IIABO intervention, and the TAHV was 60%–90% that of the control group, which was closer to the clinical results (88.9%). These results suggest that IIABO cannot effectively treat postpartum hemorrhage because of the collateral circulation and reversed flow in the uterine venules.